Village funds and village-level of economic growth: A case study in Pamekasan - Oktaviya, Yetty Dewi; Sutikno, Sutikno (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Village funds have become a significant strategy in the government's efforts to improve economic development at the village level, and village funds play a role in encouraging equitable village economic growth in Pamekasan Regency but still require a more in-depth evaluation. This research is based on the condition of even village economic growth in Pamekasan Regency villages, which is still below the average of 29.53. A study aims to analyze the relationship and how much influence there is between village funds, poverty-free villages, developing village index, and villages without disparity on the increase in the economic growth score of the village equally.  The data collection technique is a documentation technique sourced from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration. The method used in this study is multiple linear regression. The study results show that the increase in the economic growth score of the village is evenly responded to positively by villages without poverty and without inequality. On the other hand, the increase in the economic growth score of the village is responded negatively by the village fund because the higher the economic growth score of the village is even, the village fund budget will be reduced. After all, the welfare of the community begins to be achieved. The implication of the study is to provide input for related agencies and village communities in increasing the score of equitable village economic growth in Pamekasan Regency villages.